PENGARUH PENGGUNAAN PEMBELAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN LITERASI MATEMATIS SISWA SEKOLAH DASAR - Nurmalia, Meli; Ramdani, Nurlailatun; Edi Wibowo, Sarwo; Suryaningsih, Sri (Dikmat: Pendidikan Matematika, 2024)
This study investigates the impact of Project-Based Learning (PjBL) on mathematical literacy and student motivation among middle school students. Mathematical literacy is essential in developing students' problem-solving skills and critical thinking, making it crucial in today's information-driven world. This quasi-experimental study involved two groups: an experimental group that participated in PjBL and a control group that received conventional instruction. Data were collected through mathematical literacy tests, observation of student engagement, and motivation questionnaires. The results indicate that students in the PjBL group showed a significant improvement in mathematical literacy, with an increase in average scores by 26.9% compared to an 11.6% increase in the control group. PjBL also positively influenced student motivation, as evidenced by higher engagement scores and positive attitudes toward mathematics. These findings highlight the effectiveness of PjBL in not only enhancing mathematical understanding but also fostering essential 21st-century skills such as collaboration, communication, and critical thinking. The study underscores the importance of implementing contextual and interactive learning approaches like PjBL to make mathematics more relevant and engaging for students.